AN ANALYSIS OF PSYCHOSOCIAL DEVELOPMENT OF MARILYN MONROE AS SEEN FROM BLONDE (2022) - Resti Ayu Febriani; Khadija Albar Hanafi; Siska Ayu Diaz Sekarini (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
This study uses Erik Erikson's theory of psychosocial development to analyse the psychosocial stages of Marilyn Monroe in the film Blonde, released in 2022. The study looks at three main psychosocial stages using a qualitative scene analysis and a literature review. These are identity and role confusion, intimacy versus isolation, and generativity versus stagnation. A difficult childhood and lack of parental support impact Monroe's identity confusion and cause ongoing problems with self-esteem and emotional stability. The film shows her struggling to form important relationships and portrays her as a person trapped in isolation and suffering. Moreover, her aspiration for motherhood signifies generativity, but the film highlights her struggles for personal development. Although Blonde portrays Monroe's emotional struggles very well, it overlooked other essential phases of Erikson's theory that could offer a more comprehensive understanding of her psychosocial growth. More appropriate representation, including her professional accomplishments and strengths, would have provided a deeper understanding of her complex identity. This study enriches the discourse on the convergence between film, identity, and psychological development by showing how film influences the perception of historical figures and human experience.